Handbook of occupational safety and health - Mansdorf, S. Z. (Seymour Zack) 1947- (Boca Raton, Florida Wiley, 2019)
"Provides a quick, easy-to-consult source of practical overviews on wide-ranging issues of concern to those responsible for the health and safety of workers. Progresses from a general introduction on management to recognition of hazards to safety evaluations and risk assessment. New chapters include prevention by design, product stewardship, safety and health management systems, safety and health management of international operations, and EHS auditing. Offers quick overviews enabling individuals not formally trained in occupational safety to get up to speed rapidly. Many of the chapters are structured as "How to..." sections such as how to conduct an accident investigation"--Publisher.
Preceded by Handbook of occupational safety and health / edited by Louis J. DiBerardinis. 1999.
Includes bibliographical references and index.
Keywords: Occupational Health; Accidents, Occupational -- prevention & control; Handbook